Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar Seni Rupa Kelas VIII di SMPN 3 Lengayang - Ningsi, Nori Gusdia; Yahya, Yahya (ALSYS, 2025)
The purpose of this study is to find out how the learning outcomes of fine arts students in grade VIII at SMPN 3 Lengayang are influenced by the discovey learning model. Researchers conducted "experimental" research with a quantitative approach. The research design is a posttest-Only Group Design. This study involved all grade VIII students, with class VIII 1 group as the control class and class VIII group 4 as the experimental class, each with 31 students. The results of the study showed that the posttest score of art learning outcomes in the experimental class and the control class was different, with an experimental score of 70.00 and a control score of 58.03. The results of the hypothesis test showed that there was a difference in student learning outcomes both in the experimental class and the control class with a significant level = 0.05. Based on these results, it can be concluded that students in the experimental class are better at learning using the Discovery Learning learning model than students in the convetional.